Nocturnal Enuresis In Children - Asiya Kazi; Syed Ijaz Hussain Zaidi; Khemchand Mehboob; Faisal Faheem Faheem (Journal of Bahria University Medical and Dental College)
Nocturnal enuresis is one of the commonest developmental problem specially in our country. It can cause emotional family stress and social isolation of child. According to WHO if condition persist after six years of age, it should be consider as pathological. Exact cause of this condition is not known but is common in lower socio economic people due to lack of awareness about the impact of this disease on the psychology of the children. Different modalities of treatment comprising of non-Pharmacotherapy as well as pharmacotherapy are being tried but relapse rate still persist. In non-pharmacotherapy: Psychotherapy, toilet training and alarm therapy has been tried but in pharmacotherapy, monotherapy that is desmopressin and imipramine and combination of therapy that is desmopressin + oxybutynin and desmopressin + imipramine has been tried. Multiple studies are available but relapse rate till exist. Combination therapy (desmopressin + oxybutynin) is being tried in various Tertiary care Hospital of Pakistan and results are encouraging.